Comparative analysis of the allergenic characteristics and serodiagnostic potential of recombinant chitinase-like protein-5 and -12 from Sarcoptes scabiei - Shen, Nengxing (Parasit Vectors, 2021)
BACKGROUND: Scabies is caused by burrowing of the mite Sarcoptes scabiei into the stratum corneum. Currently, diagnosis via routine skin scraping is very difficult, and information on the allergenic identification of S. scabiei remains limited. METHODS: We performed comparative analysis of the serological diagnostic potential of recombinant S. scabiei chitinase-like protein-5 (rSsCLP5) and recombinant S. scabiei chitinase-like protein-12 (rSsCLP12) by measuring the levels of serum-specific IgG and IgE antibodies (Abs) as diagnostic markers. In addition, the allergenic characteristics of rSsCLP5 and rSsCLP12 were evaluated using IgE-binding experiments and skin tests. RESULTS: The IgE Abs-based indirect enzyme-linked immunosorbent assay (ELISA) methods showed high sensitivity and specificity: the rSsCLP5-based assay had 93.5% sensitivity and 94.4% specificity; the rSsCLP12-based assay had 100% sensitivity and 98.1% specificity. The specific IgE Abs in infested mouse sera could bind rSsCLP5 and rSsCLP12. In skin tests, rabbits in the rSsCLP5 and rSsCLP12 groups and positive control (histamine) groups exhibited allergic reactions. Most test sites in the rSsCLP12 group had edema, bleeding spots, and even ulcers or scabs, but such allergy symptoms were rare in the rSsCLP5 group. Moreover, the allergic history rabbit group had more severe allergic reactions and lower levels of IgE Abs compared to the healthy rabbit group in the same protein group. CONCLUSIONS: These findings validate the use of IgE Abs to rSsCLP5 and rSsCLP12 as potentially useful markers for diagnosing scabies. Moreover, both rSsCLP5 and rSsCLP12 have allergenic properties, and the potential allergen rSsCLP12 is a stronger allergen than rSsCLP5. [Image: see text] SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s13071-021-04654-0.